Detection of Vascular Reactive Oxygen Species in Experimental Atherosclerosis by High-Resolution Near-Infrared Fluorescence Imaging Using VCAM-1-Targeted Liposomes Entrapping a Fluorogenic Redox-Sensitive Probe. (9th March 2021) - Manea, Simona-Adriana; Vlad, Mihaela-Loredana; Rebleanu, Daniela; Lazar, Alexandra-Gela; Fenyo, Ioana Madalina; Calin, Manuela; Simionescu, Maya; Manea, Adrian
Abstract : Excessive production of reactive oxygen species (ROS) and the ensuing oxidative stress are instrumental in all phases of atherosclerosis. Despite the major achievements in understanding the regulatory pathways and molecular sources of ROS in the vasculature, the specific detection and quantification of ROS in experimental models of disease remain a challenge. We aimed to develop a reliable and straightforward imaging procedure to interrogate the ROS overproduction in the vasculature and in various organs/tissues in atherosclerosis. To this purpose, the cell-impermeant ROS Brite™ 700 (RB700) probe that produces bright near-infrared fluorescence upon ROS oxidation was encapsulated into VCAM-1-targeted, sterically stabilized liposomes (VLp). Cultured human endothelial cells (EC) and macrophages (Mac) were used for in vitro experiments. C57BL6/J and ApoE-/- mice were randomized to receive normal or high-fat, cholesterol-rich diet for 10 or 32 weeks. The mice received a retroorbital injection with fluorescent tagged VLp incorporating RB700 (VLp-RB700). After two hours, the specific signals of the oxidized RB700 and 1, 2-distearoyl-sn-glycero-3-phosphoethanolamine-N-(7-nitro-2-1, 3-benzoxadiazol-4-yl) (NBD-DSPE), inserted into liposome bilayers, were measured ex vivo in the mouse aorta and various organs by high-resolution fluorescent imaging. VLp-RB700 was efficiently taken up by cultured human EC and Mac, as confirmed by fluorescence microscopy and spectrofluorimetry. After systemic administration in atherosclerotic ApoE-/- mice, VLp-RB700 were efficiently concentrated at the sites of aortic lesions, as indicated by the augmented NBD fluorescence. Significant increases in oxidized RB700 signal were detected in the aorta and in the liver and kidney of atherosclerotic ApoE-/- mice. RB700 encapsulation into sterically stabilized VCAM-1-sensitive Lp could be a novel strategy for the qualitative and quantitative detection of ROS in the vasculature and various organs and tissues in animal models of disease. The accurate and precise detection of ROS in experimental models of disease could ease the translation of the results to human pathologies.